Review on Opacifying Polymeric Pigment: Reconceive Hiding - Shah, Siddhi; Mahanwar, Prakash A. (Journal of Coating Science and Technology, 2018)
A hollow core-shell latex particle synthesized through sequential semi-continuous emulsion polymerization method has served as a promising substitute to white inorganic pigments useful for the coating applications. Incorporating more amount of Titanium dioxide in the paint is a costly measure with diminishing returns. Severe paint defects such as phase separation, agglomeration or settling arises due to incompatibility between inorganic pigments and organic resins. Opaque polymer helps in minimizing the cost of Titania in surface coating formulations. It provides white appearance and hiding due to diffraction of incoming light in different directions. It has gained widespread importance over the years due to its unique structure and morphology. It has potential applications in other technologies such as micro-encapsulation, paper coatings and controlled release of drugs. Osmotic swelling – the most prominent approach involves the synthesis of an ionizable core particle which is encapsulated by another polymer functioning as shell, followed by neutralization with the addition of suitable alkali. Significant techniques have been developed including hydrocarbon encapsulation and water-in-oil-in-water emulsion in this field.